2014
DOI: 10.1016/j.psyneuen.2014.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Mice selected for extremes in stress reactivity reveal key endophenotypes of major depression: A translational approach

Abstract: Clear evidence has linked dysregulated hypothalamus-pituitary-adrenocortical (HPA) axis function to the aetiology and pathophysiology of major depression (MD), as observed in the majority of patients. Increased stress reactivity and hyperactivity of the HPA axis seem characteristic for psychotic/melancholic depression, while the atypical subtype of depression has been connected with the opposing phenotypes. However, the underlying molecular-genetic mechanisms are poorly understood. In the present study, mouse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 50 publications
3
16
0
Order By: Relevance
“…When animals were tested during early adulthood, the total distance traveled in the OF arena revealed a main effect of mouse line ( F 2,54 = 23.371, p < 0.001). Specifically, LR mice traveled shorter distances than HR and IR mice ( post hoc tests: HR vs. IR: p = 0.409, HR vs. LR: p < 0.001, IR vs. LR: p < 0.001) ( McIlwrick et al, 2016 , also shown in Figure 2A ), confirming previous findings in the SR mouse model ( Touma et al, 2008 ; Heinzmann et al, 2014 ). ELS exposure had no effect on the animals’ locomotor activity in the OFT at this time point.…”
Section: Resultssupporting
confidence: 86%
See 3 more Smart Citations
“…When animals were tested during early adulthood, the total distance traveled in the OF arena revealed a main effect of mouse line ( F 2,54 = 23.371, p < 0.001). Specifically, LR mice traveled shorter distances than HR and IR mice ( post hoc tests: HR vs. IR: p = 0.409, HR vs. LR: p < 0.001, IR vs. LR: p < 0.001) ( McIlwrick et al, 2016 , also shown in Figure 2A ), confirming previous findings in the SR mouse model ( Touma et al, 2008 ; Heinzmann et al, 2014 ). ELS exposure had no effect on the animals’ locomotor activity in the OFT at this time point.…”
Section: Resultssupporting
confidence: 86%
“…In the HR line, these include a reduced bodyweight, increased locomotor activity, hyperactive stress-coping behavior, altered sleep architecture with increased rapid eye movement (REM) sleep, and impaired cognition, akin to endophenotypes of melancholic/psychotic depression. On the other hand, LR animals show an increased bodyweight, reduced locomotor activity, passive stress-coping behavior, and intact sleep and cognitive function, in line with endophenotypes of the atypical depression subtype ( Touma et al, 2008 , 2009 ; Knapman et al, 2010a , b , 2012 ; Fenzl et al, 2011 ; Pillai et al, 2012 ; Heinzmann et al, 2014 ).…”
Section: Methodsmentioning
confidence: 78%
See 2 more Smart Citations
“…This technique of glucocorticoid metabolite quantification in fecal samples has been established in an increasing number of species and has been extensively validated for laboratory mice (Touma, Palme & Sachser, 2004). Fecal samples were collected 2 months after the end of the CPS and were analyzed for immunoreactive corticosterone metabolites using a 5α‐pregnane‐3β,11β,21‐triol‐20‐one enzyme immunoassay (EIA) according to published methods (Heinzmann et al., 2014). Before EIA analysis, the fecal samples were dried (2 hr at 80°C), homogenized, and aliquots of 0.05 g of powdered feces were extracted with 1 ml of 80% methanol.…”
Section: Methodsmentioning
confidence: 99%